Associations between mixed exposure to phthalates and latent tuberculosis infection among the general U.S. population from NHANES 2011–2012 - Bi Ran; Jiangyue Qin; Yanqiu Wu; Fuqiang Wen (Heliyon, 2024)
Background: People are constantly exposed to phthalates, but few reliable studies have focused on the connection between phthalate exposure and latent tuberculosis infection (LTBI). Methods: Data were obtained from the National Health and Nutrition Examination Survey (NHANES) database (2011–2012). The LTBI was assessed by QuantiFERON®-TB Gold-In-Tube (QFT) or tuberculin skin testing (TST). The odds ratios (ORs) and 95% confidence intervals (CIs) per log10 unit change in the concentration of phthalate metabolites were calculated using crude and adjusted logistic regression models. The relationships between mixed phthalate concentrations and LTBI were assessed using Bayesian kernel machine regression (BKMR) models. Results: According to the results of the multivariable logistic regression, in a fully adjusted model, only monobenzyl phthalate (MBZP) was negatively associated with LTBI in Q3 (OR (95% CI): 0.485 (0.286,0.823), P = 0.007). According to the restricted cubic spline (RCS) model, there was a linear dose‒response association between all 11 phthalate metabolites and LTBI (p for nonlinearity >0.05). We found a significant positive correlation between mixed phthalate metabolites and LTBI by using fully adjusted BKMR model. Conclusions: Our analysis demonstrated that LTBI in the general U.S. population is linearly linked with exposure to single or combined phthalates.